On Testing and Evaluating Service-Oriented Software. - Tsai, W. T.; Xinyu Zhou; Yinong Chen; Xiaoying Bai (Computer (00189162), 2008)
The article discusses service-oriented architecture (SOA), examining the need for developers to test increasing amounts of services. Frameworks which define and evaluate test-case potency are able to minimize testing effort yet maintain the effectiveness of the tests, the article indicates. Topics include service dependability and trustworthiness, the identification and elimination of overlapping test cases, and the reranking of existing test cases. Also discussed is the active contribution of users through Web 2.0.